The Analysis of Prepositional Phrases Found in the Carlo's Short Story Pinocchio and Its Application in Teaching Writing - Dwi Putri Amaliya Putri; Sri Widodo; Zulia Chasanah (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
Abstract. As English learners in today’s world, people must master the four skills in language learning. There are listening, speaking, reading, and writing. Writing is one of the most difficult aspects of language learning. Almost every student faces this issue. This problem prompts the researchers to conduct this study. This research is to analyze of prepositional phrases in Carlo’s short story Pinocchio. This research belongs to descriptive qualitative research. The aims of this research to find out the functions of prepositional phrases found in the Carlo’s short story Pinocchio and to describe the application of prepositional phrases in the Carlo’s short story Pinocchio in teaching writing. The data source of this research is short story of Pinocchio by Carlo Collodi. The result of the analysis shows that there are two functions of prepositional phrases found in Carlo’s short story Pinocchio. Of the 27 data found, there are 21 prepositional phrases in function as adverb (77.78%) and 6 prepositional phrases in function as adjective (22.22%). This research can be applied in teaching writing. Keywords: Prepositional Phrase, Short Story, Teaching Writing.